PENDAMPINGAN TEKNIK KONSERVASI PENYU LEKANG (Lepidochelys olivacea) DI PESISIR PANTAI LAMPUUK ACEH BESAR - Mirna Mirna; Mohamad Gazali; M Ali Sarong (Universitas Teuku Umar, 2021)
The Olive Ridley Sea Turtle (Lepidochelys olivacea), is a species of sea turtle that lives in tropical and subtropical waters with shallow waters. The olive ridley sea turtle is found laying eggs in the Indian Ocean, the Pacific Ocean, and on the beaches of large islands. The main problem is the population of the olive ridley sea turtle were experiencing the reduction significantly. The aim of this program is to undertake the accompaniment of conservation technique of The olive ridley sea turtle to coastal community Lampuuk Aceh Besar. The stages of empowerment community including monitoring, the relocation, evacuation process, quarantine, and hatching release. We done enthusiasms to follow the empowering community program. We also hope with the conservation program to keep the population of The olive ridley sea turtle at coastal area from the disturbance of preadator and poaching.